Cannabis use is not associated with increased balance disturbances in HIV-infected individuals - Patrick Kiendrebeogo; David Grelotti; Mariana Cherner; Raeanne C. Moore; Bin Tang; Ronald J. Ellis (BMC, 2021)
Abstract Background The association between long-term cannabis use and balance disturbances has not been investigated in people living with HIV (PWH). We hypothesized that long-term cannabis use in PWH might be associated with more deleterious effects on balance than in HIV seronegative individuals due to potential neurotoxic interactions between HIV and cannabis. Methods Three thousand six-hundred and forty-eight participants with and without HIV completed an interviewer-administered timeline follow-back assessment to assess lifetime days and quantity of cannabis use and other cannabis use characteristics. A structured clinical interview was used to collect any history of balance disturbance. Comparisons between HIV+ vs the HIV− groups and moderate-severe vs. no or minimal imbalance in participant characteristics (demographics, cannabis use, medication currently used, and neurological disease) were performed using Student t tests for continuous variables and Fisher's exact test for binary and categorical variables. Multivariate logistic regression was applied to determine the interaction effect of total quantity of cannabis use with HIV status on balance disturbance. Age, gender, cDSPN symptoms, gait ataxia, opioid medications, and sedatives were included as covariates in the adjusted model after variable selection. The effect sizes are presented as Cohen's d or odds ratios. Results On average, participants were 45.4 years old (SD = 11 years), primarily male (77.7%), and non-Hispanic white (48.1%). A majority of participants were HIV+ (79.1%). Four hundred thirty (11.9%) of the participants reported balance disturbances within the past 10 years. PWH were more likely to have balance disturbances than demographically matched HIV-uninfected participants (odds ratio [OR] 2.66, 95% CI 1.91-3.7). Participants with moderate-severe balance disturbances did not differ from those with no or minimal imbalance in the proportion who had ever used cannabis (73.8% vs. 74.4%; p = 0.8) (OR 1.03, 95% CI 0.80-1.32) neither did they have a higher total amount of cannabis use (4871 vs. 4648; p = 0.3) (Cohen's d 0.11, 95% CI 0.01-0.14). In the HIV− population, those with balance disturbances reported more total amount of cannabis use as compared to those with normal balance (11316 vs 4154; p = 0.007). In the HIV+ population on the other hand, there was no significant association (4379 vs 4773; p = 0.6). Conclusions We found unexpectedly that while long-term cannabis use in HIV− individuals was associated with more severe balance disturbances, there were no associations in HIV+ individuals. This suggests that cannabis use in HIV is safe with respect to balance disturbances. Given that HIV is related to persistent inflammation despite virologic suppression on antiretroviral therapy, future mechanistic studies are needed to determine whether HIV-associated inflammation contributes to the higher prevalence of balance disturbance in HIV+ individuals and whether cannabinoids have anti-inflammatory effects that mitigate HIV-associated balance disturbance.